Pemahaman Jamaah Terhadap Ibadah Salat Jumat - Arfin Radiat; Wirdati Wirdati; Mhd Zen (An-Nuha, 2022)
The implementation of Friday prayers is an order from Allah SWT to all Muslims who are already mukallaf. The law of performing Friday prayers is obligatory for every Muslim man. This obligation is stated in QS Al-Jumuah Verse 9. If you look at the facts on the ground, especially at the Air Tawar Barat Nurul Islam Mosque, most of the worshipers are still negligent in carrying out Friday prayers and if the Friday prayer time comes at 12:15 WIB, then most of the worshipers come. to the mosque at 12:10 WIB and some of them even came during the second sermon to perform Friday prayers. This study describes how Muslims (congregants of the Nurul Islam Air Tawar Barat Mosque) understand the terms and timing of Friday prayers through descriptive qualitative methods with the type of case study research in which the data were collected from 30 informants, both youths, pilgrims, adults/students, and parents. The results of the study were that most of the worshipers did not understand the conditions for Friday prayers and understood the timing of the Friday prayers, but there were some congregations, especially teenagers and adults/students whose awareness was still lacking in hastening to carry out Friday prayers. For this reason, the authors suggest religious leaders, ustadz, preachers are expected not to get tired of conveying about the implementation of Friday prayers, the virtues that are on Friday and how important it is to come to the mosque to carry out Friday prayers as well as the congregation are expected to continue to learn and understand about Friday prayer.